2013
DOI: 10.1080/02755947.2012.746246
|View full text |Cite
|
Sign up to set email alerts
|

Can Management Reduce Harvest Inequality in Recreational Fisheries?

Abstract: Harvest inequality, a situation in which most of the fish are harvested by a disproportionately small number of anglers, is a characteristic of most recreational fisheries. Harvest inequality develops when a few anglers harvest a very large number of fish or when many anglers harvest few fish. Identifying the cause of harvest inequality is critical to understanding the potential for management to reduce the inequality. Management efforts aimed at reducing the top anglers’ take will have only a modest impact if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The high level of catch inequality in this study is comparable with values reported elsewhere for rainbow trout (van Poorten & Post ), brown trout (Seekell et al . , ) and other fish species (Smith ; Baccante ). However, contrary to the studies above, a decline in catch inequality in the Tongariro River was observed over the study period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of catch inequality in this study is comparable with values reported elsewhere for rainbow trout (van Poorten & Post ), brown trout (Seekell et al . , ) and other fish species (Smith ; Baccante ). However, contrary to the studies above, a decline in catch inequality in the Tongariro River was observed over the study period (Fig.…”
Section: Discussionmentioning
confidence: 99%